Envelope‐tracking EM‐CKT simulation of nonlinearly loaded wire antennas under broadband excitations. Issue 4 (April 2015) - Subramanian, Vivek; Yılmaz, Ali E.
ABSTRACT Novel temporal sampling and interpolation schemes are presented to improve the performance of envelope‐tracking hybrid electromagnetic‐circuit simulators that express voltages, currents, and fields of interest as series of harmonic sinusoids weighted by complex time‐varying coefficients (envelopes). These schemes enable broader band simulations to be performed by expanding the range of validity of expressions that relate the envelopes of currents through nonlinear circuit elements to the envelopes of the voltages across them. Diode loaded wire antennas and antenna arrays are analyzed under broadband excitations to demonstrate the viability of the proposed schemes. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:912–918, 2015